2017
DOI: 10.1161/jaha.117.006892
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein A‐I Modulates Atherosclerosis Through Lymphatic Vessel‐Dependent Mechanisms in Mice

Abstract: BackgroundSubcutaneously injected lipid‐free apoA‐I (apolipoprotein A‐I) reduces accumulation of lipid and immune cells within the aortic root of hypercholesterolemic mice without increasing high‐density lipoprotein–cholesterol concentrations. Lymphatic vessels are now recognized as prerequisite players in the modulation of cholesterol removal from the artery wall in experimental conditions of plaque regression, and particular attention has been brought to the role of the collecting lymphatic vessels in early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…22 Apo A might prevent atherosclerosis, and its properties might be affected by its size, sequence polymorphism, the type of lipoproteins associated with it, and the inflammatory state of the vessel wall. 23 The pathogenesis of ED is similar to that of CHD. It is due to atherosclerosis, preventing the cavernous veins fromt being adequately filled, causing erection difficultly.…”
Section: Discussionmentioning
confidence: 98%
“…22 Apo A might prevent atherosclerosis, and its properties might be affected by its size, sequence polymorphism, the type of lipoproteins associated with it, and the inflammatory state of the vessel wall. 23 The pathogenesis of ED is similar to that of CHD. It is due to atherosclerosis, preventing the cavernous veins fromt being adequately filled, causing erection difficultly.…”
Section: Discussionmentioning
confidence: 98%
“…This lymphatic regression may contribute to exacerbated atherosclerosis. It has been shown that apoA-I treatment improves lymphatic transport, abolishes collecting LV permeability, and reduces aortic lipid accumulation without affecting total cholesterol levels by strengthening junctions between LECs [157]. However, no prior studies have tested whether stimulation of lymphangiogenesis or lymphatic function increases reverse cholesterol transport from atherosclerotic arteries.…”
Section: The Role Of the Lymphatic System In Atherosclerosismentioning
confidence: 99%
“…Treatment of atheroprone, LDLR −/− ; hApoB 100/100 mice with VEGF-C152S, a VEGFR-3 agonist, prevents lymphatic function impairment, advocating the correlation between LDLR modulation and lymphatic function [14]. Another study from the same research group has reported improved lymphatic transport and reduced permeability of collecting LVs in LDLR −/− mice treated with lipid-free apoA-I compared to control mice [157]. The authors observed plaque regression in the thoracic aorta of apoA-I-treated mice independent of plasma and lymph cholesterol accumulation.…”
Section: The Role Of the Lymphatic System In Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations